Medicinal Potential of Pine Trees: A Brief Review Focusing on Three Species - Qinsong Li; Qiyu Li; Anping Wang; Wenxuan Quan (BioResources)
Pinus trees are widely distributed worldwide, and pine needles, pine bark, pinecones, etc., have potential medicinal value. This paper reviews the medicinal potential of extracts from different organs of three trees of the genus Pinus in East Asia. Studies have shown that pine trees are rich in bioactive compounds, and these compounds have a variety of pharmacological activities, including antioxidation, anti-inflammatory, antibacterial, antitumor, and hypolipidemic effects. The wide range of pharmacological activities of these bioactive components is helpful for the treatment of cardiovascular diseases, inflammatory diseases, tumors, and other diseases. These findings can help promote research on the medicinal potential of Pinus and its organs to realize the efficient utilization of byproducts of pine resources.